Primary Membranous Nephropathy - what do we know today? - Wais, Marcin; Warchoł, Konrad; Jasiura, Adam; Wójcik, Aleksandra; Giżewska, Kamila (Quality in Sport, 2023)
Introduction: Primary membranous nephropathy (PMN) is a common cause of nephrotic syndrome in adults, characterized by the deposition of immune complexes in the glomerular basement membrane. Aim of this study: evaluate the features of PMN such as incidence, pathology, clinical features and assess the effectiveness of immunosuppressive therapy. Materials and Methods: The review was based on articles found in PubMed database, using keyword „primary membranous nephropathy” with appropriate sufixes. Results: PMN is a challenging disease that requires a multidisciplinary approach to diagnosis and management. Laboratory tests, including assessment of autoantibodies and complement levels, are essential for the diagnosis of PMN. Immunosuppressive therapy can be effective in inducing remission in a significant proportion of patients. Conclusions: Further research is needed to optimize the duration and intensity of immunosuppressive therapy, and to evaluate the role of newer therapies such as rituximab and belimumab.